ANALISIS TENTANG MOTIVASI ORANG TUA MEMILIH PONDOK PESANTREN SEBAGAI SARANA PEMBINAAN MORAL DI SMA PONDOK PESANTREN BABUSSALAM PEKANBARU - Saputri, Rika; Hambali, Hambali; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on some parents who choose the education unit, they are not motivated to entrust their children to public school but choose to leave their children in boarding school. Education is developing the ability in the form of character and civilization of dignified nation in ragka educate the life of the nation. The purpose of this study was to find out how the motivation of parents to choose boarding school as a means of moral coaching in SMA pesantren Babussalam pekanbaru pesantren as well as intrinsic and extrinsic motivation. The type of research used is quantitative descriptive research, and the sampling technique used is incidental sampling. This research was conducted by questionnaire to 47 respondents, it is known that the motivation of parents to choose pesantren as a means of moral coaching in SMA Pondok Pesantren Babussalam Pekanbaru is very high with percentage of 77% and 23% with high category. parents motivation to choose pesantren cottage is supported by 2 indicators that is intrinsic and extrinsic motivation. SMA intrinsic motivation parents choose pesantren as a means of moral building in Pondok Pesantren Babussalam Pekanbaru, obtained information that 89% in category is very high, 11% in high category. Then on extrinsic motivation parents choose pesantren as a means of moral coaching in SMA Pondok Pesantren Babussalam Pekanbaru obtained information that 38% in category is very high, 60% in category high, 2% in low category.Keywords: Motivation, Parents, Choosing Pondok Pesantren